The Impact of Dedication on College Student Stamina: An Econometric Analysis - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Barros, María Claudia Pacheco (Journal of Ecohumanism, 2024)
The present study analyzes the relationship between dedication and vigor in first-year university students in the city of Montería, using a quantitative approach based on a simple linear regression model. The research is based on the premise that academic commitment, represented in the dedication of students, influences their levels of vigor, understood as energy, endurance and enthusiasm in the development of academic activities. From the analysis of a sample of 50 university students, it was found that dedication has a positive and significant effect on vigor, with a coefficient of 0.5151 (p < 0.001). In addition, the validation of the model through statistical tests confirmed compliance with the regression assumptions, guaranteeing the reliability of the results. It is concluded that students with higher levels of dedication experience greater vigor in their academic activities, which suggests the importance of strengthening pedagogical strategies that promote student engagement in higher education.